Electronic decay and fragmentation dynamics of iodomethane, multiply core-ionized by photoabsorption of intense XFEL pulses - Motomura, K.; Kukk, E.; Wada, S.; Nagaya, K.; Fukuzawa, H.; Mondal, S.; Tachibana, T.; Ito, Y.; Koga, R.; Sakai, T.; Matsunami, K.; Rudenko, A.; et al. (My University, 2014)
We have studied charge migration and dissociation in iodine-substituted methane molecules using extremely intense and short 5.5 keV free electron laser pulses from the SACLA XFEL facility. Multiple core ionization down to I 2p subshells creates highly charged molecular states, the fragmentation of which was studied by ion momentum imaging multiparticle coincidence technique. We report experimental and modeling results on various dissociation pathways, fragment momentum correlations, and kinetic energy releases.